2021
DOI: 10.7189/jogh.11.04043
|View full text |Cite
|
Sign up to set email alerts
|

Physician burnout in the Eastern Mediterranean region: influence of gender and related factors – Systematic review and meta-analysis

Abstract: Background While recent reviews highlight high burnout prevalence among physicians in the World Health Organization’s (WHO) Eastern Mediterranean Region (EMR), there has been a limited exploration into the role of gender and related factors in this problem. Methods We conducted a systematic review and meta-analysis of studies on the prevalence of physician burnout and its relationship to gender, physician specialties, and age in the WHO’s EMR based on the Cochrane Handb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 55 publications
(60 reference statements)
1
24
1
Order By: Relevance
“…Although burnout has been extensively described among health professionals worldwide and in the Eastern Mediterranean region ( 33 ), limited research was performed among academic university staff, particularly in low middle-income countries. In developed countries, burnout among faculty has been an important issue for decades with increasing responsibilities and tasks diversity ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although burnout has been extensively described among health professionals worldwide and in the Eastern Mediterranean region ( 33 ), limited research was performed among academic university staff, particularly in low middle-income countries. In developed countries, burnout among faculty has been an important issue for decades with increasing responsibilities and tasks diversity ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Norlund et al, 2010;Dyrbye et al, 2011;Aguwa et al, 2014;Granek et al, 2016;Huang et al, 2019;Eden et al, 2020;Gold et al, 2021;Lee et al, 2021;McPeek-Hinz et al, 2021). A few other studies reported only marginal gender differences in physician burnout prevalence (Linzer et al, 2002;te Brake et al, 2003;Śliwiński et al, 2014;El Ghaziri et al, 2019;Doraiswamy et al, 2021). The differences may be due to sampling, research settings, cultures, assessment methods for burnout, and variable cut-off valuesat least 142 unique burnout definitions or subscale criteria (Rotenstein et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies found that female health workers had a higher risk of burning out (Aguwa et al, 2014;Granek et al, 2016;Eden et al, 2020;Loscalzo et al, 2021;McPeek-Hinz et al, 2021), and some suggested that educational level, socioeconomic status and working hours were associated with burnout in female physicians (Norlund et al, 2010). On the contrary, a few studies found no gender differences in physician burnout (Linzer et al, 2002;te Brake et al, 2003;Doraiswamy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We screened the titles and abstracts of 604 articles (after removing duplicate articles) and performed full-text review of 137 articles. We deemed 16 reviews to be relevant for inclusion, of which eight were systematic reviews 6,8,[15][16][17][18][19][20] and eight were narrative reviews (Figure 1). 3,[21][22][23][24][25][26][27] Copyright © 2023 JPOSNA® www.jposna.org…”
Section: Overviewmentioning
confidence: 99%